Soil fertility survey in the “agreste” area of Pernambuco, Brasil - Dantas, Humberto da Silveira; Gomes, Ivan Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
This work was carried out at Taquaritinga do Norte, a county located in the "Agreste area" of Pernambuco State. To verify the distribution, area sizes and characteristics of different types of soil, ten soil profiles considered representatives of the soil mapping units for that area were collected and studied. Procedures for the field observation, using Contour maps, were those recommended by the “Soil Survey Manual”. Methods and techniques recommended for macronutrient studies were used in the laboratory. In general, the soils were predominantly coarse sand, especially in the surface horizon, but there was a gradual increase in clay with depth, i.e. when the textural classification changed from loam-clay-sand to clay. Quantity of exchangeable cation was medium. In general, contents of carbon, nitrogen and phosphorus were low. On a large scale, the soils of that specific area of Taquaritinga do Norte can be classified within the following great soil groups: Red-Yellow Latosol, Red Yellow Podzolic, Sodic-Planasol, Eutrophic Regosol and Eutrophic Alluvial Soil.